Haematological changes induced by the deltamethrin a synthetic pyrethroid technical grade and 11% EC (Decis) in the fish ctenopharyngodon idella (valenciennes) - Srinivasa Rao G.; K. Balakrishna Naik; S. Satyanarayana; N. Gopala Rao (Journal of Innovations in Pharmaceutical and Biological Sciences, 2018)
Haematological changes induced in the fish, Ctenopharyngodon idella after exposure to the two toxicants deltamethrin technical grade and 11% EC (Decis) are studied. They are erythrocytes (RBC) White Blood Corpscules (WBC), Haemoglobin (Hb), Haematocrit (Ht), Mean Corpscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH) and Mean Corpscular Haemoglobin Concentration (MCHC) when the fish are exposed to lethal and sublethal concentrations of both the toxicants. Among the blood parameters studied changes/alterations are observed as decrement in RBC, HB and Ht whereas WBC is increased. Accordingly, the calculated values also changed. A culturable fish, one, like in the present study, needs to be carefully monitored in cultarable water quality which when contaminated either directly or indirectly